trategi Pemanfaatan dan Pelestarian Ikan Sidat secara Berkelanjutan Berbasis Masyarakat di Sungai Cimandiri, Kabupaten Sukabumi - Lia Sutiani; Sugeng Heri Suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The Japanese eel fish (Anguilla spp.) is a high economical consumption fish with high nutritional content. Japanese eel fish according to high protein (16.4%) And vitamin A amounted to 4700IU. In addition, a Japanese eel fish (glass eel) also containing unsaturated fatty acids (EPA and DHA). One of the areas in Indonesia that has a great potential for glass eel resources is the province of West Java precisely at the estuary of Cimandiri River, Sukabumi. High export demand resulted in an increased arrest effort at Palabuhanratu Bay to threaten its population. This study aims to examine the activities of the Japanese Eel fish seed arrest accompanied by the sustainable management of the Japanese Eel fish resources in the estuary of Cimandiri River, West Java. The threat of a Japanese Eel resource on the Cimandiri River is caused by several factors. Such factors are such as environmental pollution, uncontrolled overfishing or arrest, and low awareness of the public to conduct sustainable use of the Japanese eel fish. Therefore, the solution that can be applied is community based management. Community-based management of this Japanese eel resource is a management with a community-based cultivation strategy. The cultivation of Japanese eel is a step in the preservation of Japanese eel as well as impact on the improvement of social life and community economy. Key words: Cimandiri River, eel fish, sustainable management